1968
DOI: 10.1037/h0025494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of signal and stimulus rates on vigilance performance.

Abstract: 2 experiments investigated the relative effects of critical signal rate, normal noncntical signal rate, and critical signal probability on detection in a visual vigilance task In all conditions Ss had to monitor a clock display for a period of 54 min The results of both experiments suggested that normal signal rate may be of greater importance in a vigilance situation than either critical signal rate or critical signal probability In general, both percentage of detections and percentage of stimuli falsely resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Reinerman-Jones et al Taub and Osborne (1968) later confirmed these results. Another study, conducted by Bakan and Manley (1963), involved blindfolding a portion of the group of observers while they listened to a 48-min tape recording of single digit numbers with critical signals for detection being three odd digits in a row.…”
supporting
confidence: 66%
“…Reinerman-Jones et al Taub and Osborne (1968) later confirmed these results. Another study, conducted by Bakan and Manley (1963), involved blindfolding a portion of the group of observers while they listened to a 48-min tape recording of single digit numbers with critical signals for detection being three odd digits in a row.…”
supporting
confidence: 66%
“…An increasing number of studies have been reported that lend support to this conclusion. The general finding is that vigilance performance is inversely related to the event rate and that the event rate is a more important factor, within limits, than either signal probability or signal frequency (Jerison, 1967;Loeb & Binford, 1968;Mackworth, 1968;Taub & Osborne, .1968). In these experiments, pacing of the event rate was achieved by presenting regularly recurring events at various interevent intervals.…”
mentioning
confidence: 99%